The quality and variation of spirometry reads for testing lung function in children in sub Saharan Africa - Maduna, Dumsile Nontokozo (Department of Public Health and Family Medicine, 2020)
Background: Lung function assessments have become the cornerstone of understanding the ever-increasing burden of non-communicable respiratory conditions worldwide. The introduction of pulmonary function testing (PFT) has made maximal expiratory flow/volume (MEFV) measurements the basis of lung function assessments and spirometry the most widely used diagnostic tool for lung function testing. The effectiveness of spirometry to distinguish between normal and abnormal lung function has been realised in adults; however, there is an observed history of misinterpretation in children. The quality of measurements remains a major concern in children and good quality measurements are critical in the diagnosis of any health condition as well as understanding the burden of abnormal lung function in children in low and middleincome countries (LMICs). Objective: This study describes the quality and variation of spirometry reads for evaluating lung function in children in a Malawian population. Methods: This study was conducted according to a protocol developed and granted ethical approval by the Faculty of Health Sciences Human Research Ethics Committee, University of Cape Town (HREC REF 669/2018). The protocol describes the parent study data collection, project analysis plans and ethical and other considerations. Current literature on lung function using spirometry was systematically reviewed and synthesised. The literature review included primary studies and review articles that included spirometry measurement in children from settings in Africa and other low- and middle- income countries. The descriptive study involves secondary analysis of data contributed by the Children Lung Health study, a cross-sectional survey conducted in Malawi. Spirometry measurements from 802 healthy children aged 6-8 years, inexperienced in performing MEFV manoeuvres, are evaluated. Data in the primary study were collected by means of a structured questionnaire which included items on socio-demographic characteristics and spirometry was performed according to the American Thoracic Society and European Respiratory Society (ATS/ERS) guidelines using an Easy on-PC spirometer in the participant‘s home. The ATS/ERS standards for adults and the modified recommendations for children were applied to evaluate quality. Descriptive statistics were used to describe the quality of spirometry indices and univariable logistic regression to identify and describe variables that are predictors of quality. Results: The findings of the study were that many children (34%) failed to reach the complete ATS/ERS quality standards. The end-of-test criteria (forced expiratory time) was the most difficult to meet for children and if this is not met (i.e. exhalation is not complete), the forced vital capacity (FVC) will be underestimated leading to it being misinterpreted. More than 30% of the children failed to meet the repeatability criteria when the relative differences for FVC and forced expiratory volume in the first second (FEV1) was used, yet they are the most appropriate in paediatric practice as compared to absolute differences. Young children were more likely to produce poor quality spirometry as compared to older children. Conclusion: Young children may perform acceptable spirometry according to the modified ATS/ERS recommendations; however, the quality remains suboptimal. Further modification of the already lowered quality standards, seems to be the viable option, but the implications of this clinically has not been evaluated. Other alternatives need to be explored for this group.